Bahasa Inggris - Sheren Novita Ara (Jurnal Akuntansi, Manajemen dan Ekonomi, 2022)
Nata de coco is a processed product whose main component is coconut water, such as a transparent white jelly. The nata de coco company named PT Shenovia is a business unit that oversees the management of nata de coco. PT Shenovia is spread across several provinces in Indonesia, one of which is in the province of West Java. The purpose of this study was to determine the effect of sales forecasts on PT Shenovia. The data used in this study is the actual data owned by the company. The data taken is PT Shenovia's sales data from 2016 to 2021. The data is used to determine the sales forecast to be obtained in 2022. This company uses three methods in time series analysis and calculates forecasting errors using the MAPE (Mean Absolute Percent Error) method. ), the results obtained are the least square method of 67%, the moving average method of 2.91% and the semi-average method of 2.27%. So it can be concluded that the best forecasting results are the moving average and semi-average methods, because they have an accuracy value of <10%, which means the ability of the forecasting model is very good.